SERUM ANTIOXIDANT DERANGEMENTS AS DIAGNOSTIC AND PROGNOSTIC MARKER IN BIPOLAR DISORDER: A COHORT STUDY. - Yadav, Narveer; Yadav, Aarti; Rikhari, Praveen; Sinha, Vishal (Student’s Journal of Health Research Africa, 2024)
Background Bipolar disorder causes recurrent mania/hypomania and depression. According to the inflammatory idea, oxidative stress and antioxidants may be imbalanced throughout this illness. This study investigates the role of non-enzymatic antioxidants - serum uric acid, serum albumin, and serum bilirubin in different phases of bipolar disorder and compares them with healthy controls. Method Three groups were studied in this cohort research. One group had bipolar affective disorder patients with manic episodes, the second with depressed episodes, and the third with healthy controls. Serum uric acid, albumin, and bilirubin were measured before and after 4 weeks of treatment. The YRMS scale was used for manic episodes and the HAM-D scale was used for depressive episodes to assess disease severity. Results The study included 107 participants: 53 bipolar maniacs, 24 bipolar depressives, and 30 healthy controls. Bipolar mania was associated with considerably higher uric acid levels (5.40 mg/dl) compared to bipolar depression (4.09 mg/dl) and healthy controls (3.16 mg/dl) (p<0.001). Serum albumin levels were lower in bipolar depression (3.08 mg/dl) compared to mania (4.37 mg/dl) and healthy controls (4.60 mg/dl) (p<0.001). Results found no difference in serum bilirubin (p=0.367). Serum uric acid was reduced in bipolar mania (4.08 mg/dl) and depression (3.24 mg/dl) after 4 weeks (p<0.001), but albumin rose in depression (4.03 mg/dl) (p<0.001). Bipolar depression also increased serum bilirubin (0.72 mg/dl, p=0.01). Conclusion These findings suggest a potential role for serum uric acid and albumin as biomarkers in bipolar disorder, reflecting oxidative stress in these patients. This might also have a role in monitoring the progress and treatment of the patients. Recommendation Antioxidants can play a significant role in bipolar disorder but more research work is required. Further research with larger cohorts, consideration of confounding factors, and including measurement of more antioxidant molecules is essential to validate these findings.